Immersive Virtual Reality as a teaching aid for anatomy - Laura Mason (Proceedings of the Virtual and Augmented Reality to Enhance Learning and Teaching in Higher Education Conference 2018, 2019)
Anatomy is a discipline where students are required to identify structures of the human body. It is typically a topic which challenges students due to the large volume of terms and content they are required to understand. This study was designed to investigate whether Virtual Reality (VR) as an innovative approach to teaching could improve both student experience and attainment in this subject area. A specifically developed VR platform was created in which Medical Engineering students (N = 42) were asked to individually compete to assemble a human skeleton in both the fastest time and with the fewest errors. This gamification in an immersive environment was hypothesised to increase students’ understanding and retention of anatomical information and was compared to studying from a set of traditional notes. The results showed a 10 % greater improvement in test scores with VR over the use of notes (non-significant, P = 0.141). In the longer term those who participated in the study performed significantly better on the end of module examination (P = 0.012) suggesting measurable learning gain from the experience more widely. Students responded positively to the use of VR in this context and expressed an interest in seeing more VR as part of their anatomy education and their Higher Education experience more broadly.